Amiloride reduces portal hypertension in rat liver cirrhosis. Issue 6 (13th May 2010) - Steib, Christian J; Hennenberg, Martin; Beitinger, Frigga; Hartmann, Anna C; Bystron, Markus; De Toni, Enrico N; Gerbes, Alexander L
Abstract : Objective: This study aimed to investigate the effect of amiloride on portal hypertension. Amiloride is known to inhibit Na + /H + exchangers on activated hepatic stellate cells. Methods: Liver cirrhosis in rats was induced by bile duct ligation (BDL) or thioacetamide (TAA) administration. The effects of zymosan for Kupffer cell (KC) activation or a thromboxane (TX) analogue (U46619) were tested in isolated perfused livers of cirrhotic rats and in vivo. Downstream mechanisms were investigated using Rho kinase inhibitor (Y-27632) or amiloride. Acute and chronic effects of amiloride and canrenoate on portal pressure were compared in perfused livers and in vivo. TXB2 efflux was measured by ELISA. The phosphorylation state of moesin (p-moesin) as an indicator of Rho kinase activity and expression of the thromboxane synthase were assessed by western blot analyses. The activity of hepatic stellate cells was analysed by western blot and staining for α-smooth muscle actin (α-SMA). Results: In BDL rats, KC activation via zymosan increased portal pressure. This was attenuated by the Rho kinase inhibitor Y-27632. Increased thromboxane efflux following zymosan infusion remained unaltered by Y-27632. The infusion of amiloride attenuated zymosan- and U46619-induced increases in portal perfusion pressure. In vivo, direct administration of amiloride, but not of canrenoate, lowered portal pressure. In TAA and BDL rats, treatment with amiloride for 3 days reduced basal portal pressure and KC-induced increases in portal pressure whereas canrenoate had no effect. In livers of amiloride-treated animals, the phosphorylation state of moesin and the number of α-SMA positive cells were reduced. Conclusions: Amiloride lowers portal pressure in rat liver cirrhosis by inhibition of intrahepatic vasocontraction. Therefore, patients with cirrhosis and portal hypertension may benefit from amiloride therapy.